Synthesis, characterization and antimicrobial activity of nanochitosan and chitosan encapsulated zinc oxide nanoparticles against bacteria and fungus - ., Sivanthaperumal; Ansari, Thaminum (International Journal of Advanced Chemistry, 2022)
In recent years, Nanochitosan and chitosan encapsulated Zinc oxide nanoparticles have gained tremendous attention related to their unique properties such as exhibit antimicrobial properties. On that account, synthesis of nanochitosan and chitosan encapsulated zinc oxide nanoparticles by ionotropic gelation method have fascinating properties such as eco-friendly, biodegradability, biocompatibility, bioactivity, nontoxicity and polycationic nature. Impact of nanochitosan and chitosan encapsulated zinc oxide nanoparticles on biological functions depends on its morphology, particle size, exposure time, concentration, pH, and biocompatibility. They are more effective against microorganisms such as, namely Staphylococcus aureus, E. coli, Salmonella typhimurium, and Klebsiella pneumoniae. In this paper, synthesis of nanochitosan, chitosan encapsulated zinc oxide and compare their potential applications as an antimicrobial agents were discussed. The nanochitosan and chitosan encapsulated zinc oxide nanoparticles have been characterized by Ultraviolet-Visible Spectroscopy (UV), Fourier Transform Infrared Spectroscopy (FT-IR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) were also examined.Â Â